OPTIMALISASI KOMBINASI SLUDGE, ARANG SEKAM, DAN KOMPOS UNTUK EFISIENSI PEMUPUKAN DAN PRODUKTIVITAS JAGUNG MANIS - Fitriyani, Indri Hapsari; Furqoni, Hafith; Sintia, Mira; Putra, Aldani M (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
Consumption of sweet corn has increased from 2021 to 2024. To meet the growing market demand, sweet corn production must be carried out in a sustainable, economical, efficient, and environmentally friendly manner. The use of a combination of sludge, rice husk charcoal, compost, and inorganic fertilizer was tested to enhance corn plant growth and productivity. The study was conducted at the Cikabayan Experimental Farm, IPB University, using a Randomized Complete Block Design (RCBD) with five treatment levels and three replications. The results showed that treatment S2H1 (75% sludge + 75% rice husk charcoal + 30% compost + 75% NPK) exhibited the best vegetative and generative growth (stem diameter, number of leaves, ear length, biomass weight per plot, and ear weight per plot). The S1H1 treatment (100% sludge + 75% rice husk charcoal + 30% compost + 75% NPK) showed improved biological and chemical soil quality (pH, organic carbon, total nitrogen, total phosphorus, and base saturation). All treatments resulted in an R/C ratio above 1, indicating economically viable potential. The results indicate demonstrate that the combined use of sludge and organic materials allows NPK fertilizer inputs to be reduced by 25%, supporting sustainable agriculture.